A2-type cyclin is required for the asymmetric entry division in rice stomatal development - Qu, Xiaoxiao (Journal of experimental botany, 2018)
In rice, and other major cereal grass crops, stomata are arranged in linear files parallel to the long growth axis of leaves. Each stomatal unit comprises two dumbbell-shaped guard cells flanked by two subsidiary cells. These morphological and developmental characteristics enable grass stomata to respond to environmental changes more efficiently. Cyclin-dependent kinases (CDKs) and their cyclin partners co-ordinate cell proliferation and differentiation during the development of multicellular organisms. In contrast to animals, plants have many more types and members of cyclins. In Arabidopsis, four A2-type cyclins (CYCA2s) function redundantly in regulating CDKB1 activity to promote the asymmetric division for stomatal initiation and the symmetric division of guard mother cells (GMCs). In this study, we examine the function of the single A2-type cyclin in rice, OsCYCA2;1, as well the single B1-type CDK, OsCDKB1;1. Cross-species complementation tests demonstrated that OsCYCA2;1 and OsCDKB1;1 could complement the defective stomatal phenotypes of Arabidopsis cyca2 and cdkb1 mutants, but also could suppress DNA endoduplication and cell enlargement. The early asymmetric divisions that establish the stomatal lineages are often missing within the stomatal cell files of OsCYCA2;1-RNAi rice transgenic lines, leading to a significantly reduced stomatal production. However, GMC divisions are not disrupted either in OsCYCA2;1-RNAi or in OsCDKB1;1-RNAi rice transgenic lines as expected. Our results demonstrate a conserved but diverged function and behavior of rice A2-type cyclins, which might be associated with the distinct stomatal development pathways between rice and Arabidopsis